Sustainable Strategy in the Development of Mangrove Ecotourism in Pasar Rawa Village, Langkat Regency - Ratna Sari; Muhtar Ardansah Munthe; Aulia Putra Daulay (Postgraduate, University of Mataram, 2023)
Pasar Rawa Village has natural tourism potential that has not been managed optimally, one of which is mangrove ecotourism. Mangrove ecotourism is one of the efforts to conserve forest resources whose management positively impacts the environment and social economy of the community. This research aims to determine the right strategy for developing mangrove ecotourism in Pasar Rawa Village so that its management is sustainable. The research began by determining the strengths, weaknesses, opportunities and challenges of ecotourism development through direct observation, interviews, distribution of questionnaires and literature studies, then the development strategy was analyzed using SWOT analysis. The research results show that Pasar Rawa Village Mangrove Ecotourism is in quadrant I which supports aggressive growth policies and eleven ecotourism development plans refer to the regulations of the minister of tourism and the creative economy.